The health-related quality of life in children with IgA vasculitis - Zhou, Juan; Nie, Min; Song, Zixia; Shen, Xing (Frontiers in Pediatrics, 2025)
IntroductionThe objective of this study was to investigate the health-related quality of life (HRQOL) in children diagnosed with IgAV and explore factors influencing it, aiming to provide insights for rehabilitation of these children.MethodsThis study enrolled 114 children diagnosed with IgAV at Bazhong Central Hospital between January 2019 and January 2023. 51 healthy children undergoing health check-ups during the same period were enrolled in control group. Data on sociodemographic and clinical characteristics, as well as health-related quality of life scores, were collected. The Pediatric Quality of Life Inventory Measurement Models 4.0 (PedsQL™ 4.0) was utilized to assess the HRQOL of these children and to explore correlations among different dimensions of quality of life. General linear regression models were applied to analysis of influencing factors of the HRQOL of children with IgAV.ResultsThe health-related quality of life scores in all dimensions for children with IgAV were lower compared to those of healthy children. Recurrence of IgAV was negatively correlated with all dimension scores and the total HRQOL score (P < 0.05). Children with exercise-induced onset showed lower physiological functioning scores compared to those without exercise-induced onset. Emotional functioning scores were lower in children with self-funded medical care compared to those with Medicare. Children with medication duration longer than 1 week exhibited higher social functioning scores.ConclusionsThe HRQOL of IgAV children is lower than that of healthy children. Relapse, exercise, the payment method and regularity of medications affect children's health-related quality of life.